Investigation of Antioxidant Compositions and Antioxidative Activities of Ethanol Extract of Alstonia boonei Stem Bark (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Oxidative stress is the major mechanism of action employed by many drugs, xenobiotics and toxicants that generate reactive metabolites in the body to elicit adverse reactions when there are insufficient antioxidants to neutralise the excess reactive metabolites. Objectives: This study evaluated antioxidant compositions and antioxidative activities of ethanol extract of Alstonia boonei stem bark with the view of understanding its ameliorative potentials on oxidative stress. Materials and Methods: Thirty-six rats divided into 6 groups of 6 rats each was used for this study. Group 1 served as normal control, group 2-6 were carbon tetrachloride-induced oxidative stress which served as treatment groups. Group 2 was untreated, group 3 was treated with silymarin (100 mg/kg) while group 4-6 were treated with the extract 100, 200 and 500 mg/kg body-weight for 28 days respectively. The animal study and antioxidant compositions of the extract were analysed using standard methods.Results: The extract was found to rich in antioxidant components such as phenols, flavonoids, β-carotene and lycopene. The extract showed high DPPH (2, 2-diphenyl-1-picrylhydrazyl) and nitric oxide radical scavenging activities and high ferric reducing antioxidant power with increasing concentrations. The significant (P < 0.05) reduction in antioxidant enzymes activities and increased level of lipid peroxidation caused by the carbon tetrachloride induction were significantly (P < 0.05) reversed, in the extract-treated groups relative to the normal control. Conclusions: These findings suggest that the extract possesses antioxidative properties and can be used in the management of oxidative stress and its related disease conditions